2021
DOI: 10.21203/rs.3.rs-846460/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome In Neonates Associated With SARS-CoV2 infection- A case series.

Abstract: Multisystem inflammatory syndrome(MIS) in children (MIS-C) associated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV2) is well recognised in children, however, rarely reported in newborns. We describe a case series of 20 neonates who were diagnosed as MIS in neonates (MIS-N). We grouped cases into three categories as Most likely MIS(5), Possible MIS(9) and Unlikely MIS(6). All neonates had high titres of SARS CoV 2 IgG antibodies and were negative for SARS CoV 2 antigens. The most common clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Multisystem inflammation, coronary dilation, 11 thrombosis, AV conduction block, and ↑ inflammatory markers 12 13…”
Section: Key Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…Multisystem inflammation, coronary dilation, 11 thrombosis, AV conduction block, and ↑ inflammatory markers 12 13…”
Section: Key Pointmentioning
confidence: 99%
“…More et al have presented five similar cases of MIS-C-like clinical features in neonates (MIS-N). 13 Diggikar et al reported a case of early neonatal acute SARS-CoV-2 infection followed by a multisystem inflammatory response. 14 These and the other reports outlined in ►Table 1, [15][16][17][18][19][20][21] suggesting an overlap between four possible manifestations of COVID-19 during the neonatal period (►Table 2).…”
mentioning
confidence: 99%
“…98 Neonatal cases of MIS-C (Neonatal MIS-C, or MIS-N) are rarely reported, and their clinical presentation is not well-established. 99 100 101 102 103 Orlanski-Meyer et al reported a 6-week-old infant with severe gastrointestinal symptoms, anemia, elevated D-dimers, ferritin, hypoalbuminemia, and thrombocytosis then thrombocytopenia. Echocardiography in this infant showed normal coronary arteries with mitral regurgitation.…”
Section: Neonates With Confirmed Covid-19 and Mis-cmentioning
confidence: 99%
“…Increase in the occurrence of multisystem inflammatory syndrome in neonates (MIS-N) has been reported within the last few months, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 including a recent case report describing a newborn with acute respiratory distress syndrome intubated on day 1 of life and diagnosed with possible MIS-N on day 4, treated with intravenous immunoglobulins (IVIGs) and steroids. The newborn also developed encephalopathy and severe endotheliitis of coronary arteries.…”
Section: To the Editormentioning
confidence: 99%
“…Till January 18, 2022, more than 50 cases of MIS-N have been reported. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 As in older infants and children, the lack of a diagnostic test makes the clinical diagnosis challenging in non-specific cases. This may be specifically applicable to newborns and preterm ones as well, where there is a wide differential diagnosis of cases with acutely worsening conditions.…”
Section: Prompt Recognition Of Mis-nmentioning
confidence: 99%